Effects of milk and chocolate milk on strength and power in healthy females - Wee, Crystal. (2013)
Resistance exercise may lead to muscle damage and decrements in subsequent performance. Plain milk has not been compared to chocolate milk (CM), though both have been found to aid in muscle protein synthesis and improve subsequent exercise performance. This study compares the effects of low-fat milk (LM) versus low-fat CM (LCM) on strength and power in eumenorrheic females. It was hypothesised that there would be no difference between LM and LCM for post-exercise recovery. Eight healthy females ([Mean±SD] Age: 23.4±3.1yr; BMI: 20.9±1.7kg/m2) were randomized to consume isovolumetric amounts of LM, LCM or a water control (CON) in a repeated-measures crossover manner immediately after performing a unilateral knee extension resistance exercise (RE) bout. Extensor peak torque, work per repetition, peak power and total work done were assessed using muscular function tests immediately post-RE and 4 hours after passive rest. The RE bout generally did not induce significant differences in muscular performance compared to baseline measurements. Significant differences were found between LCM and LM for peak torque (7.00±7.29Nm vs. - 4.63±13.16Nm; P=0.036), and for peak power between LCM and LM (14.13±15.41W vs. - 5.00±13.94W; P=0.017), and LCM and CON (14.13±15.41W vs. 1.00±5.93W; P=0.012) at isokinetic speed 60/60°/s, with no significant differences between conditions for other variables. Results suggest that LCM is more suitable than LM or CON for isokinetic muscular performance recovery. The novel finding was that only LM demonstrated isometric muscular performance recovery after post-RE consumption. Young healthy females may consume LM or LCM as effective recovery beverages according to their performance demands.